Postgraduate supervision as an advanced teaching and learning practice: Exploring the scholarship link - Wilkinson, AC (South African Journal of Higher Education, 2011)
In the light of viewpoints that pedagogy has been an obvious missing category in considerations of scholarly supervisory work, the author argues that the existing theory on the (more established) scholarship of teaching and learning (SoTL) may be successfully adapted to make it highly applicable to supervisory scholarship. Research supervision has, however, been acknowledged as an advanced and complex kind of teaching-learning activity with its specific products and challenges. Special knowledge and skills are therefore needed. The point of departure is that SoTL (and consequently the scholarship of postgraduate supervision, SoPgS) integrates Boyer’s four types of scholarship (discovery, integration, application and teaching). In addition to suggestions for the adaptation and/or extension of the SoTL, a developmental road for SoPgS is considered, with culmination in a proposal for different levels of performance in postgraduate supervision. Two related issues are touched upon: acceptable ‘products’ of a SoPgS and possible criteria for recognition and reward.